2023
DOI: 10.1227/neu.0000000000002763
|View full text |Cite
|
Sign up to set email alerts
|

From Text to Insight: A Natural Language Processing-Based Analysis of Topics and Trends in Neurosurgery

Mert Karabacak,
Alexander J. Schupper,
Matthew T. Carr
et al.

Abstract: BACKGROUND AND OBJECTIVES: Neurosurgical research is a rapidly evolving field, with new research topics emerging continually. To provide a clearer understanding of the evolving research landscape, our study aimed to identify and analyze the prevalent research topics and trends in Neurosurgery. METHODS: We used BERTopic, an advanced natural language processing-based topic modeling approach, to analyze papers published in the journal Neurosurgery. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Nevertheless, despite the rigorous methodology used in this study 1 and the significant results reported by the authors, the study depended on the data extracted from a single journal, which does not reflect the global neurosurgical literature. As mentioned by the authors, many other limitations are existing, including the use of linear models in data analysis, the potential metadata inconsistency, and the lack of other comprehensive validation studies.…”
Section: Fundingmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, despite the rigorous methodology used in this study 1 and the significant results reported by the authors, the study depended on the data extracted from a single journal, which does not reflect the global neurosurgical literature. As mentioned by the authors, many other limitations are existing, including the use of linear models in data analysis, the potential metadata inconsistency, and the lack of other comprehensive validation studies.…”
Section: Fundingmentioning
confidence: 99%
“…In this review article, 1 Karabacak et al used a new topic-modeling methodology in evaluating the dynamic nature of neurosurgical research within the domain of the Neurosurgery journal, based on its position at the forefront of the neurosurgical fraternity journals. They used the bidirectional encoder representations and transformers (BERT) method, an advanced Natural Language Processing (NLP)–based topic modeling approach.…”
mentioning
confidence: 99%
See 2 more Smart Citations